The effectiveness of a multidisciplinary QI activity for accidental fall prevention: Staff compliance is critical - Ohde Sachiko; Terai Mineko; Oizumi Aya; Takahashi Osamu; Deshpande Gautam A; Takekata Miwako; Ishikawa Ryoichi; Fukui Tsuguya (BMC, 2012)
Abstract Background Accidental falls among inpatients are a substantial cause of hospital injury. A number of successful experimental studies on fall prevention have shown the importance and efficacy of multifactorial intervention, though success rates vary. However, the importance of staff compliance with these effective, but often time-consuming, multifactorial interventions has not been fully investigated in a routine clinical setting. The purpose of this observational study was to describe the effectiveness of a multidisciplinary quality improvement (QI) activity for accidental fall prevention, with particular focus on staff compliance in a non-experimental clinical setting. Methods This observational study was conducted from July 2004 through December 2010 at St. Luke's International Hospital in Tokyo, Japan. The QI activity for in-patient falls prevention consisted of: 1) the fall risk assessment tool, 2) an intervention protocol to prevent in-patient falls, 3) specific environmental safety interventions, 4) staff education, and 5) multidisciplinary healthcare staff compliance monitoring and feedback mechanisms. Results The overall fall rate was 2.13 falls per 1000 patient days (350/164331) in 2004 versus 1.53 falls per 1000 patient days (263/172325) in 2010, representing a significant decrease (p = 0.039). In the first 6 months, compliance with use of the falling risk assessment tool at admission was 91.5% in 2007 (3998/4368), increasing to 97.6% in 2010 (10564/10828). The staff compliance rate of implementing an appropriate intervention plan was 85.9% in 2007, increasing to 95.3% in 2010. Conclusion In our study we observed a substantial decrease in patient fall rates and an increase of staff compliance with a newly implemented falls prevention program. A systematized QI approach that closely involves, encourages, and educates healthcare staff at multiple levels is effective.